Examining Syntactic Complexity in EFL Learners’ IELTS Writing Performance - Komara Suhendar (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study investigated IELTS writing performance among EFL learners with advanced proficiency in terms of syntactic complexity. Following Lu’s proposal (2011) on the indices of syntactic complexity, the writings were analysed through several measures, such as length of production, sentence complexity, subordination, coordination, and particular structures (e.g. complex nominals and verb phrases). The findings of this study reveal that. The findings reveal that learners construct sentences primarily through clausal structures, with a mean sentence length of 16.55 words and an average of 2.26 clauses per sentence. At the same time, they also demonstrate dominance in the use of complex nominals and coordinate phrases, which accounted for 4.49 per T-unit and 5.85 per T-unit, respectively. While these findings partially support the view that growth in one domain can lead to a reduction in another, they also present a more nuanced perspective. Specifically, the results suggest that advanced learners tend to employ clausal complexity to achieve cohesion and phrasal complexity to ensure conciseness in their writing. These findings extend the existing literature on syntactic complexity by emphasizing the interplay between clausal and phrasal constructions in advanced learners’ writing.